2022
DOI: 10.1177/17531934211073866
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mTOR inhibitors (sirolimus) in isolated limb overgrowth: a systematic review

Abstract: We systematically assessed the literature on the use of sirolimus for the treatment of isolated limb overgrowth conditions and its various modalities of administration in PubMed, Scopus, Ovid MEDLINE, Web of Science, Google Scholar, Cochrane Database of Systematic Reviews, references of journals and grey literature using pre-trialled Medical Subject Headings terms and articles. Eleven articles were included, and 39 patients were identified for review. Sirolimus was given orally in 38 patients and topically in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…Common surgical options include epiphysiodeses, osteotomies, soft-tissue debulking, nerve resection, carpal tunnel releases, toe transfers and amputations 16. Recently, sirolimus, an mTOR inhibitor is considered as an adjuvant treatment for isolated limb overgrowth conditions 17. However, due to rare incidence and variability in clinical features of macrodactyly, there are limited long-term quantitative data and standard treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common surgical options include epiphysiodeses, osteotomies, soft-tissue debulking, nerve resection, carpal tunnel releases, toe transfers and amputations 16. Recently, sirolimus, an mTOR inhibitor is considered as an adjuvant treatment for isolated limb overgrowth conditions 17. However, due to rare incidence and variability in clinical features of macrodactyly, there are limited long-term quantitative data and standard treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…16 Recently, sirolimus, an mTOR inhibitor is considered as an adjuvant treatment for isolated limb overgrowth conditions. 17 However, due to rare incidence and variability in clinical features of macrodactyly, there are limited long-term quantitative data and standard treatment protocols. In the study, we performed epiphysiodesis in patients with growth potential, and investigated postoperative growth in terms of the longitudinal and appositional growth.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the potential use of rapamycin in the treatment of children affected with PROS should be carefully considered, taking numerous side effects into account. However, a recent review demonstrated only mild side effects in the treatment of isolated overgrowth with oral rapamycin [37]. Sandbank et al reported good responses to topical sirolimus in the case of vascular malformations, such as in the KTS-part of the PROS spectrum [38].…”
Section: Nonsurgical Treatmentmentioning
confidence: 99%

Macrodactyly

Giżewska-Kacprzak,
Śliwiński,
Nicieja
et al. 2024
Children